Mutagenicity of Recombinant Antihemophilic Factor (GC-γAHF) - Shin, Minki; Kim, Byungsoo; Mar, Woongcheon; Fang, Mingzhu; Son, Jangwon; Kim, Minyoung; Kwak, Hyungil; Bae, Miok; Byun, Taeho; Park, Songyong; Chun, Bokhwan; Byun, Jonghwan; An, Gilhwan; Lee, Bumjoon; Cho, Myunghaing (Arzneimittelforschung, 2000)
This study was carried out to evaluate the mutagenic potential of recombinant antihemophilic factor VIII (GC-γAHF). Salmonella typhimurium (S. typhimurium) reversion assay with/without histidine moiety, chromosomal aberration assay on Chinese hamster lung (CHL) fibroblast cells and in vivo micronucleus assay using mouse bone marrow cells and supravital micronu-cleus assay using peripheral blood were performed. GC-γAHF containing histidine did show inconsistent and irregular mutagenic effects on S. typhimurium TA98, TA100, TA1535 and TA1537 both in the absence and presence of the metabolic activation system, however, GC-γAHF without histidine showed no mutagenic effects regardless of the metabolic activation system, thus suggesting that the histidine moiety in GC-γAHF might cause inconsistent mutagenic effect. Also GC-γAHF did not increase the number of cells having structural or numerical chromosome aberration in the cytogenetic test. In classical and supravital micronucleus assay, no significant increases were observed in the occurrence of micronucleated polychromatic erythrocytes and micronucleated peripheral lymphocytes in male ICR mice. These results strongly indicate that GC-γAHF has no genetic toxicity under these experimental conditions.
Keywords: Antihemophilic factor, Ames test, chromosomal aberration assay; micronucleus assay, supravital micronucleus assay